2005
DOI: 10.1007/s10661-005-4773-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient transfer by runoff from sewage sludge amended soil under simulated rainfall

Abstract: Abstract. Wastewater sludges are used in agriculture as soil amendment and fertilizer, with regard to their organic matter and nutrient content. However, availability of nitrogen and phosphorus from sludge-amended soils and their transfer in runoff may lead to eutrophication of downstream surface water. The aim of this study is to establish and compare the effect of two different sludges on these transfers: an anaerobically digested and thermically stabilised sludge (Seine-Aval treatment plant, sludge no. 1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…While biosolids application was comparable in the current study and the aforementioned, the TN and TP concentrations in runoff were relatively high by comparison to anaerobically digested or alkaline‐stabilized biosolids in similar studies (e.g., Elliott et al, 2005; Quilbé et al, 2005; White et al, 2010). However, TP concentrations were comparable to those in runoff from anaerobically digested or lime‐stabilized biosolids studied by Penn and Sims (2002), and from biosolids produced by biological nutrient removal processes (Elliott et al, 2005; Penn and Sims, 2002).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…While biosolids application was comparable in the current study and the aforementioned, the TN and TP concentrations in runoff were relatively high by comparison to anaerobically digested or alkaline‐stabilized biosolids in similar studies (e.g., Elliott et al, 2005; Quilbé et al, 2005; White et al, 2010). However, TP concentrations were comparable to those in runoff from anaerobically digested or lime‐stabilized biosolids studied by Penn and Sims (2002), and from biosolids produced by biological nutrient removal processes (Elliott et al, 2005; Penn and Sims, 2002).…”
Section: Resultssupporting
confidence: 66%
“…Mobilization of nutrients in anaerobically digested biosolids was not surprising. As in the current study, Quilbé et al (2005) and Penn and Sims (2002) found an increase in TP in runoff from anaerobically digested biosolids. This was true regardless of whether the treatment process used Fe to immobilize P (Penn and Sims, 2002).…”
Section: N and P In Runoffsupporting
confidence: 80%
See 2 more Smart Citations
“…In order to simulate rainfall, a portable 1.27-cm 30W single-nozzle (Tossell et al, 1987) was placed 1.7 m above the soil surface ( Figure 3). It was suspended from two iron stakes connected by a PVC (polyvinyl chloride) pipe (Tossell et al, 1987;Nolan et al, 1997;Quilbe et al, 2005). A nozzle pressure of 48.3 kPa was produced with a gasoline-powered pump to produce a mean rainfall intensity of 7 cm ⁄ 30 min on a 0.5-m 2 plot.…”
Section: Simulated Runoff and Water Samplingmentioning
confidence: 99%